2020
DOI: 10.1007/s40200-020-00492-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome using international diabetes federation, National Cholesterol Education Panel- Adult Treatment Panel III and Iranian criteria: results of Tabari cohort study

Abstract: Background Metabolic syndrome is defined by co-incidence of multiple metabolic disorders such as central obesity, high triglycerides, low HDL, hyperglycemia and high blood pressure, which increases the risk of cardiovascular disease and diabetes. The aim of this study was to estimate the prevalence of metabolic syndrome using Adult Treatment Panel III (ATP-III), International Diabetes Federation (IDF) and Iranian criteria in large-scaled population based cohort study and to determine the concordance between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
1
14
2
2
Order By: Relevance
“…(1) Waist circumference ø 102 cm for men and ø 88 cm for women, (2) triglyceride ø 150 mg/dL or use of medication, (3) HDL \ 40 mg/dL in men or \50 mg/ dL in women or use of medication, ( 4) hypertension (systolic blood pressure ø 130 mmHg or diastolic pressure ø 85 mmHg) or use of medication, and (5) hyperglycemia (FBS ø 100 mg/dL or use of medication). 3 Elevated serum ALT, AST, GGT, and ALP levels were defined according to the reference range of the laboratory in cohort center. Elevated serum both ALT and AST levels were defined as .40 U/L (males) and .35 U/L (females).…”
Section: Definition Of Termsmentioning
confidence: 99%
“…(1) Waist circumference ø 102 cm for men and ø 88 cm for women, (2) triglyceride ø 150 mg/dL or use of medication, (3) HDL \ 40 mg/dL in men or \50 mg/ dL in women or use of medication, ( 4) hypertension (systolic blood pressure ø 130 mmHg or diastolic pressure ø 85 mmHg) or use of medication, and (5) hyperglycemia (FBS ø 100 mg/dL or use of medication). 3 Elevated serum ALT, AST, GGT, and ALP levels were defined according to the reference range of the laboratory in cohort center. Elevated serum both ALT and AST levels were defined as .40 U/L (males) and .35 U/L (females).…”
Section: Definition Of Termsmentioning
confidence: 99%
“…Determination of serum tumor necrosis factor-alpha (TNF-α) levels in metabolic syndrome patients from Saudi population Organization (WHO), and International Diabetes Foundation (IDF)and. 4 Cytokines are immune mediators, which are chemically complex peptides that perform various regulatory functions, and their role has been connected to MetS and its different constituents. 5 In the MetS, the excessive deposition of fat in adipose tissue provides an inflammation environment development triggered by the intrusion of various cells like lymphocytes, macrophages, and suppressor cells.…”
Section: Original Articlementioning
confidence: 99%
“… 3 As the metabolic syndrome is a complex anomaly, the definition for disease categorization has been explained by various organizations like Adult Treatment Panel III (ATP III), National Cholesterol Education Program (NCEP), the World Health Organization (WHO), and International Diabetes Foundation (IDF)and. 4 …”
Section: Introductionmentioning
confidence: 99%
“…1 It has been reported increases the risk of type 2 diabetes and cardiovascular diseases. 2,3 Patients with MetS have a 2x higher risk of death and a 3x higher risk of having a heart attack and stroke compared to healthy people. 4 A study in Kairo showed that 33.3% of patients with MetS had vessel occulation and more severe coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%
“…6 According to the International Federation of Diabetes criteria, the global prevalence of MetS is 25%. 2 An unhealthy lifestyle is associated with an increased risk of MetS. 7 A long-term high-fat, low-fiber diet can cause damage to the intestinal barrier, leading to chronic inflammation due to the presence of pathogenic bacteria and their products released into the systemic circulation.…”
Section: Introductionmentioning
confidence: 99%